2010
DOI: 10.1097/sih.0b013e3181d3ee0b
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Randomized Controlled Trial of Hybrid Obstetric Simulation Training for Undergraduate Students

Abstract: High-fidelity simulation can be used to train and evaluate learning. The use of patient-actors during simulation improves students' communication skills. Future research should assess whether this translates into better communication with real patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…The SBL helps students identify their strengths and weaknesses and motivate them in learning as they build self-confidence in their clinical competency through simulated training. 8 Also, it has been reported 9 that the awareness of communication technique, 10 clinical decision making, and general health conditions 11,12 contribute to enhancing the capabilities of health professionals. The simulation-problem-based learning (S-PBL), which is a combined model of the two learning methods discussed previously, is widely applied in many academic fields including the study of nursing.…”
mentioning
confidence: 99%
“…The SBL helps students identify their strengths and weaknesses and motivate them in learning as they build self-confidence in their clinical competency through simulated training. 8 Also, it has been reported 9 that the awareness of communication technique, 10 clinical decision making, and general health conditions 11,12 contribute to enhancing the capabilities of health professionals. The simulation-problem-based learning (S-PBL), which is a combined model of the two learning methods discussed previously, is widely applied in many academic fields including the study of nursing.…”
mentioning
confidence: 99%
“…Furthermore, our findings support the work of Kneebone et al 22 30 31 and Higham et al 17 who found that integrated models can effectively teach skills which are often taught separately. The use of hybrid simulation in an obstetric environment has been shown to improve procedural scores and clinical outcomes compared to didactic teaching alone,18 32 33 while bench model training for gynaecological procedural skills has been reported as reliable and valid 14 34. Despite numerous studies investigating the ethics and legality of intimate examinations and the recent highlighting of patient safety concerns by medical regulatory authorities,35 36 many of the students in our study were unaware of the potential assault charge for examining a woman without explicit consent.…”
Section: Discussionmentioning
confidence: 99%
“…Poor communication is a key factor in up to 70% of complaints and litigation cases 15 16. Hybrid simulation (combining a manikin with a patient actor) has been shown to be effective for practising skills which are usually taught separately (procedural and communication)17 and is superior to didactic lectures in obstetrics 18. Previous studies, however, have not compared hybrid models to training with manikins alone in the practice of pelvic (gynaecology) examinations and have relied on self-assessment rather than an objective external review of the students’ performance 18…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Scenario Content Validity First, because one of the objectives of the simulation centered on communication with the patient and patient-centered care, realistic patient communication cues were essential.…”
Section: Theory and Designmentioning
confidence: 99%